2019
DOI: 10.1080/08998280.2019.1573405
|View full text |Cite
|
Sign up to set email alerts
|

Transverse myelitis associated with yellow fever vaccination

Abstract: Yellow fever is a mosquito-borne viral hemorrhagic fever endemic to sub-Saharan Africa and South America associated with significant morbidity and mortality. The use of a live attenuated vaccine can prevent yellow fever, but vaccine-associated neurologic disease has been reported and is a safety concern. We present the case of a previously healthy 35-year-old active-duty man who received the yellow fever vaccine prior to deployment and subsequently developed progressive neurologic dysfunction consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The most common reported vaccine-related myelitis was due to influenza vaccine (H1N1) (7 out of 20 cases) [ 19 – 25 ] followed by myelitis due to hepatitis B vaccine (3 of the 20 cases) [ 12 14 ]. Other causes of vaccine-related transverse myelitis included COVID-19 (SARS-CoV-2) vaccine [ 42 ], Japanese B encephalitis [ 11 ], Measles, Mumps and Rubella (MMR), inactivated Rabies vaccine [ 18 ], Diphtheria, tetanus and acellular pertussis (DTaP) vaccine [ 7 ], typhoid Vi capsular polysaccharide vaccine [ 17 ], oral Polio vaccine (OPV) [ 10 ], Yellow fever [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common reported vaccine-related myelitis was due to influenza vaccine (H1N1) (7 out of 20 cases) [ 19 – 25 ] followed by myelitis due to hepatitis B vaccine (3 of the 20 cases) [ 12 14 ]. Other causes of vaccine-related transverse myelitis included COVID-19 (SARS-CoV-2) vaccine [ 42 ], Japanese B encephalitis [ 11 ], Measles, Mumps and Rubella (MMR), inactivated Rabies vaccine [ 18 ], Diphtheria, tetanus and acellular pertussis (DTaP) vaccine [ 7 ], typhoid Vi capsular polysaccharide vaccine [ 17 ], oral Polio vaccine (OPV) [ 10 ], Yellow fever [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transverse myelitis (TM) is a very uncommon condition, and rarer is the vaccine-associated TM. However, some studies have reported its occurrence following administration of other vaccines, including diphtheria, tetanus toxoids and pertussis vaccine [ 7 ], measles, mumps, and rubella (MMR) virus vaccine [ 8 , 9 ], oral poliovirus vaccine [ 10 ], Japanese encephalitis virus vaccine [ 11 ], hepatitis B vaccine [ 12 14 ], yellow fever vaccine [ 15 , 16 ], typhoid vaccine [ 17 ], rabies vaccine [ 18 ], and seasonal influenza virus vaccine [ 19 – 25 ]. In addition, only oral polio vaccine was found to have a pathogenic causal relationship while other vaccines showed a temporal relationship to TM due to a common denominator such as an adjuvant [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postinfectious TM accounts for approximately 30-60% of cases of idiopathic TM (14, 85, 86) and is more common in children than adults (87). It is often monophasic with neurologic symptom onset 2-6 weeks after a minor infectious episode, such as a viral upper respiratory tract infection, or vaccination (85,86,(88)(89)(90). Although the exact pathophysiology is not completely understood, postinfectious TM is thought to involve an autoimmune inflammatory response triggered by cross-reactivity of pathogen and host antigens (91).…”
Section: Postinfectious Myelitismentioning
confidence: 99%
“…YEL-AND tends to affect young infants, immunocompromised individuals, and the elderly. The incidence of YEL-AND is 2.2 cases per 100,000 vaccine doses among vaccine recipients ≥60 years old [110][111][112]. In 2009, the first case of encephalitis in an infant was confirmed to be caused by YF vaccine virus transmitted via breastmilk [113][114][115].…”
Section: Safety Profile Of Yellow Fever Vaccinesmentioning
confidence: 99%